2017
DOI: 10.1007/s00405-017-4560-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the bacteriology of rhinosinusitis

Abstract: Evaluating gender differences in pathogens involving sinonasal tract disease in patients undergoing nasal surgery for chronic and recurrent rhinosinusitis (C/R RS). Retrospective analysis of 164 positive sinonasal swab cultures taken during endoscopic sinonasal surgery between the years 2006 and 2013. Study population included 79 (48.8%) female patients and 84 (51/2%) males with a mean age of 47.3 (13-88) years. Positive Staphylococcal growth was found in 38 (23.2%) patients, positive anaerobic growth in 25 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Males may have higher clinical disease measures due to greater incidence of nasal polyps, which has been demonstrated 45 . Sex differences in the microbiome may contribute to differences in symptoms and responsiveness to therapy; Golan et al noted that when compared with females, males undergoing ESS had significantly higher rates of staphylococcal, anaerobic, and polymicrobial growths on sinonasal cultures 46 . At this time, the sinus microbiome has been associated with disease presence and treatment outcome, but its role in disease severity and specific symptom domains is unclear 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Males may have higher clinical disease measures due to greater incidence of nasal polyps, which has been demonstrated 45 . Sex differences in the microbiome may contribute to differences in symptoms and responsiveness to therapy; Golan et al noted that when compared with females, males undergoing ESS had significantly higher rates of staphylococcal, anaerobic, and polymicrobial growths on sinonasal cultures 46 . At this time, the sinus microbiome has been associated with disease presence and treatment outcome, but its role in disease severity and specific symptom domains is unclear 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the impact of sex in CRSwNP and AERD is not yet fully elucidated, studies evaluating e.g. the nasal microbiome in patients with CRS suggest differences in microbial colonization in women and men [24]. Furthermore, sex and gender specific differences might differ in CRS phenotypes like CRsNP, CRSwNP patients and patients suffering from AERD.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible reasons for this. There may be a gender difference in the bacteriology of CRS, as male patients are more likely to have Staphylococcus aureus identified in cultures taken during functional endoscopic sinus surgery (FESS) . Another factor may be the distribution of the inflammatory changes in the sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…16 A subsequent study looking at the most recent NSAS from 2006 showed no significant difference in sinus surgery by gender, 8 whereas data from the SASD of Florida found that men had more procedures per ESS case than women. 9 One conclusion that can be drawn from these 24 Another factor may be the distribution of the inflammatory changes in the sinuses. In a study looking specifically at the gender differences in patients with CRS who elected to proceed with FESS, women were shown to have less-severe findings on preoperative imaging despite having worse preoperative quality of life symptom scores.…”
Section: Discussionmentioning
confidence: 99%